COVID-19 and the Black Death: Nutrition, frailty, inequity, and mortality - Katherine D. VAN SCHAIK; Sharon N. DeWITTE (Journal of Health and Social Sciences)
Introduction: COVID-19 has challenged governments, healthcare systems, and individuals, drawing at- tention to the limits of modern technology and the extent of social inequity. Such challenges have directed attention to historical epidemics as repositories of data that could contribute to effective public health stra- tegies and prognostic modeling. In light of the well-established correlation between frailty and mortality from COVID-19, this paper investigates the relationship between frailty, inequity, and mortality in the set- ting of the Black Death of 1346 – 1353, in order to identify trends over time in populations at the greatest risk of mortality during pandemics. Methods: A comparative review examining relationships between frailty and mortality during the fourte- enth century Black Death and the current COVID-19 pandemic was conducted. Data related to the Black Death are derived from osteological analyses of remains from mass plague graves in the United Kingdom, and data related to COVID-19 are derived from the United States, Italy, and China. Results: Nutrition – often a consequence of socioeconomic status – plays a crucial role in pandemic mor- tality. During the Black Death, people with pathological indicators that can reflect undernourishment due to inadequate caloric intake were more likely to die of plague. In the COVID-19 pandemic, higher obesity rates among populations of lower socioeconomic status in the United States reveal similar relationships among nutrition, frailty, inequity, and pandemic mortality. Conclusion: Nutrition – often a consequence of socioeconomic status – has a crucial role in risks of mor- tality. Our analysis underscores the importance of addressing nutrition and frailty in present and future discussions of the prevention and mitigation of pandemics.